Pemasaran Jasa Pendidikan di Lembaga Pendidikan Anak Usia Dini - Arsyia Fajarrini; Fetty Ernawati (ABNA : Journal of Islamic Early Childhood Education, 2020)
Every early childhood educational institution competes to offer its advantages to attract the interests of prospective students. Therefore, it is needed between the teacher and the principal in creating innovation. RA AR Rasyid has obtained A accreditation twice, namely in 2007-2012 and 2020-2025. The problem in this study is that not all teachers are involved in marketing socialization in the community, where the target marketing for every outcome is the same. . This study aims to determine the marketing strategy of education services at RA AR Rasyid and the implementation of marketing mix at the institution. This study uses descriptive qualitative method which was carried out at RA AR Rasyid Ngemplak Kartasura in the Academic Year of 2019/2020 in the span of September 2019 to March 2020. From this study it can be concluded that; first, RA AR Rasyid markets its education services through socialization in various community gathering. RA AR Rasyid applies four of the seven marketing mixes, namely, promotion, products, prices, and places.